ELABORATION STAGES OF A SOCIAL CAMPAIGN PROJECT FOR PROGRAM OF MOTOR ACTIVITIES FOR DEFICIENTS (PROAMDE) (Fiep Bulletin - online, 2014)
This article has the objective of present's elaboration stages to realize a social campaign for the Program of Motor Activities for Deficients (PROAMDE), using bibliography, documental and field researches to fundament an elaboration of strategies action and all creative process. The PROAMDE has no lucrative ends, that try to reaches the necessities of the Manaus' deficients, the social propaganda is an instrument to confirmed positive image faced with society, once the society is informed about the work developing for the program, conquest new partnerships and stimulating the quittance of human values and social responsibility. For the elaboration of the campaign, the stages let a systematic information, which is selected through the briefing and research, organizing the communication planejement, the campaign planejement, and media; and finally, its structured in the creation, resting to be produced and propagated to get concrete results. The proposal to adapt a social propaganda for the divulgation, investment and turn society conscious, it can stimulate another social project to adapt the same idea, we just need the participation and support of businesses to this objective.
Keywords: Social propaganda; Publicity campaign; PROAMDE